2016
DOI: 10.1074/jbc.m115.707208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Interaction of the Human Protein Tyrosine Phosphatase Non-receptor Type 4 (PTPN4) with the Mitogen-activated Protein Kinase p38γ

Abstract: The human protein tyrosine phosphatase non-receptor type 4 (PTPN4) prevents cell death induction in neuroblastoma and glioblastoma cell lines in a PDZ⅐PDZ binding motifs-dependent manner, but the cellular partners of PTPN4 involved in cell protection are unknown. Here, we described the mitogen-activated protein kinase p38␥ as a cellular partner of PTPN4. The main contribution to the p38␥⅐PTPN4 complex formation is the tight interaction between the C terminus of p38␥ and the PDZ domain of PTPN4. We solved the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 30 publications
9
30
1
Order By: Relevance
“…Studies have demonstrated that PTPN4 regulates neuronal cell homeostasis by protecting neurons against apoptosis [30]. In neuroblastoma and glioblastoma cell lines, mitogen-activated protein kinase p38 γ served as a cellular partner of PTPN4 [35]. This interaction is mediated by the binding of C terminus of p38 γ to the PDZ domain of PTPN4, which antagonizes the catalytic autoinhibition of PTPN4, leading to cell apoptosis [24, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that PTPN4 regulates neuronal cell homeostasis by protecting neurons against apoptosis [30]. In neuroblastoma and glioblastoma cell lines, mitogen-activated protein kinase p38 γ served as a cellular partner of PTPN4 [35]. This interaction is mediated by the binding of C terminus of p38 γ to the PDZ domain of PTPN4, which antagonizes the catalytic autoinhibition of PTPN4, leading to cell apoptosis [24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…In neuroblastoma and glioblastoma cell lines, mitogen-activated protein kinase p38 γ served as a cellular partner of PTPN4 [35]. This interaction is mediated by the binding of C terminus of p38 γ to the PDZ domain of PTPN4, which antagonizes the catalytic autoinhibition of PTPN4, leading to cell apoptosis [24, 35]. Indeed, silencing of PTPN4 or p38 γ gene leads to massive cell death in human osteosarcoma cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…PTPN4 normally protects cells from apoptosis but addition of ligands for the PTPN4 PDZ domain resulted in a marked induction of cell death [ 66 ]. Subsequent studies revealed that the PTPN4 PDZ domain in fact auto-inhibits the enzyme’s catalytic activity, and this is abrogated upon binding of a PDZ domain ligand [ 67 , 68 ]. The segment linking the PDZ and PTP domain in PTPN4 is also contributing to this regulatory principle [ 69 , 70 ].…”
Section: Inhibiting and Augmenting Ptp Activitiesmentioning
confidence: 99%
“…Recently, a bidentate molecule (113B7) that prevents the syntenin PDZ domain from binding targets like mutant EGFR (EGFRvIII) was shown to increase radiosensitivity and decrease growth of glioma tumors in vivo [ 154 ]. Then, there is the example of PTPN4, of which the enzyme activity is autoinhibited by its PDZ domain [ 67 , 68 , 69 , 70 ]. Upon ligand binding, the PDZ-mediated inhibition is released and PTPN4 no longer protects glioblastoma cells from apoptosis [ 66 ].…”
Section: Untying Gordian Knots In Glioblastomasmentioning
confidence: 99%
“…The PBM of p38γ has the highest affinity of all PBM from endogenous partners of PTPN4 and has a similar affinity to the optimized pro-death 13-amino acids peptide Cyto8-RETEV. Both peptides are efficient inducers of cell death after their intracellular delivery 11 , 12 . Furthermore, we showed that the PDZ domain of PTPN4 inhibits the phosphatase activity, while a PBM bound to the PDZ domain abrogates the auto-inhibition of the catalytic activity of PTPN4 11 , 13 .…”
Section: Introductionmentioning
confidence: 99%